Prevalence of acute and chronic wounds – with emphasis on pressure ulcers – in integrated continuing care units in Alentejo, Portugal. Issue 4 (13th April 2020) - Furtado, Kátia A. X.; Infante, Paulo; Sobral, Ana; Gaspar, Pedro; Eliseu, Graça; Lopes, Manuel
Abstract: The aim of the study was to describe the prevalence and general characteristics of acute and chronic wounds in 2018 in Alentejo (Portugal) continuing care units. In order to look at associations, wound characteristics studied were location, type, place of acquisition, number, and duration, and patient characteristics were sex, age, and presence of risk factors. During the first 2 weeks of February 2018, a total of 770 patients were assessed at continuing care units of Alentejo. Of these, 135 exhibited wounds, a prevalence of 17.5%. Almost two out of three patients (63%) had arterial hypertension, slightly more than one in three (37%) had a stroke and/or immobility and 30% had diabetes. Of the total wounds identified, 18% were acute wounds and 82% were chronic wounds. Of the 24 acute wounds, traumatic wounds (76%), and surgical wounds (22%) were the most prevalent. The four types of pressure ulcers represented 80% of the chronic wounds. The median duration of the pressure ulcers was 5.5 months and 25% had duration over 10 months.